Teachers' Perception Regarding the Impact and Performance of Mid - Day Meal Scheme in Sangrur District of Punjab - Kanchan, Rani; Jain, Pardeep (Prabandhan: Indian Journal of Management, 2013)
The Government of India, both at the Centre and State levels, has been playing an important role in quantitative and qualitative expansion of education. The Mid-Day Meal Scheme is one of the main schemes which has been launched by the Central Government of India with a view to enhance enrollment, retention, attendance, and simultaneously improving nutrition level among students. The present study has been carried out with the aim to examine teachers' perceptions regarding quality and quantity aspects of the Mid-day Meal Scheme and to analyze the impact of the Mid-Day Meal Scheme on the health of the students in three educational development blocks in Sangrur district of Punjab. For this research, data were collected from 103 schools. One teacher per school associated with the Mid-Day Meal Scheme was interviewed using a pre-designed questionnaire. It was found that the majority of the teachers had a positive attitude regarding the impact and performance of the Mid-Day Meal Scheme. They were satisfied with the quality and quantity of food provided to the students. In addition, the teachers were of the opinion that this scheme has given a positive direction to the health and learning ability of the underprivileged students by eliminating class room hunger.